ON THE NEED TO STUDY KAZAKH-KARAKALPAK RELATIONS (Spectrum Journal of Innovation, Reforms and Development, 2022)
The article covers the views on the relations of the Karakalpak-Kazakh peoples. For the purpose of covering the topic of the article, works of Russian and European scientists were used.